200 years of isotope and chemical records in a firn core from Hercules Neve, northern Victoria Land, Antarctica - STENNI, Barbara; CAPRIOLI R.; CIMINO L.; CREMISINI C.; FLORA O.; GRAGNANI R.; LONGINELLI A.; MAGGI V.; TORCINI S. (Annals of Glaciology, 1999)
A 42.2 m firn core was collected at the Hercules Neve plateau (100 km inland and 2960 m a.s.l.), northern Victoria Land, during the 1994-95 Italian Antarctic Expedition. Chemical (Cl-, NO3-, SO42- and H2O2) and isotope (δ18O) analyses were performed to evaluate the snow-accumulation rate at this site. Tritium measurements were performed in the upper part of the core to narrow down the dating of the core. High nssSO42- concentrations seem to be related to some explosive volcanic eruptions, such as Tambora (AD 1815) and the preceding event called 'Unknown' (AD 1809), Coseguina (AD 1835), Makjan (AD 1861), Krakatoa (AD 1883) and Tarawera (AD 1886). A comparison between the seasonal variations observed in the isotope and chemical profiles was carried out in order to reduce the dating uncertainty, using the tritium and the volcanic markers as time constraints. A deposition period of 222 years was determined. The 3 year smoothed δ18O profile shows more negative values from the bottom of the core (dated AD 1770) throughout the 19th century, suggesting 'cooler' conditions, in agreement with other East Antarctic ice-core records. Subsequently, a general increase in δ18O values is observed. The calculated average snow-accumulation rates between the above-mentioned time markers are 111-129 kg m-2 a-1.